Broad-spectrum therapeutic potential of 4-phenylbutyrate in neurological and systemic diseases of viral and non-viral origin - Bobat, Fatima; Wu, David; Tu, Ethan; Kapoor, Divya; Sharma, Pankaj; Adams, Joseph S.; Orameh, Chima; Yadavalli, Tejabhiram; Date, Abhijit; Shukla, Deepak (Frontiers in Pharmacology, 2025)
4-Phenylbutyrate (4-PBA), initially recognized for treating urea cycle disorders, has emerged as a potent therapeutic agent with broad-spectrum potential. As a chemical chaperone, 4-PBA modulates protein folding and reduces endoplasmic reticulum stress. 4-PBA has demonstrated efficacy in treating ocular herpes simplex virus type 1 (HSV-1) infection and HSV-1-induced encephalitis, highlighting its potential as a novel anti-herpetic therapy. Beyond its antiviral properties, 4-PBA’s therapeutic reach extends to neurological disorders linked to HSV-1 infection, including Parkinson’s, Alzheimer’s, Huntington’s diseases, and primary open-angle glaucoma. Furthermore, 4-PBA shows promise in treating a diverse array of conditions beyond neurology. Its potential has been explored in atherosclerosis, Adriamycin-induced cardiac injury, non-alcoholic fatty liver disease, rifamycin-induced liver injury, chronic kidney disease, diabetic nephropathy, NSAID-induced kidney injury, and chronic wound healing. This review synthesizes the multifaceted therapeutic potential of 4-PBA, emphasizing its role as a broad-spectrum agent capable of addressing a wide range of pathological conditions, particularly its role in combating HSV-1 and associated neurological disorders. The growing evidence suggests that 4-PBA may be a versatile and valuable addition to the therapeutic arsenal against multiple diseases.